2020
DOI: 10.21037/atm-20-5845
|View full text |Cite
|
Sign up to set email alerts
|

Surface-based morphometry study of the brain in benign childhood epilepsy with centrotemporal spikes

Abstract: Background: The study aimed to explore cortical morphology in benign childhood epilepsy with centrotemporal spikes (BECTS) and the relationship between cortical characteristics and age of onset and intelligence quotient (IQ). Methods: Cortical morphometry with surface-based morphometry (SBM) was used to compare changes in cortical thickness, gyrification, sulcal depth, and fractal dimension of the cerebral cortex between 25 BECTS patients and 20 healthy controls (HCs) with two-sample t-tests [P<0.05, family-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Lastly, Z. Li, Zhang, Wang, et al (2020) evaluated FD in benign childhood epilepsy with centrotemporal spikes (BECTS) but did not observe significant differences in FD between patients and HC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, Z. Li, Zhang, Wang, et al (2020) evaluated FD in benign childhood epilepsy with centrotemporal spikes (BECTS) but did not observe significant differences in FD between patients and HC.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the retrieved studies evaluated FD in patients with epilepsy (Cook et al, 1995; Free et al, 1996; Z. Li, Zhang, Wang, et al, 2020; Lin et al, 2007). Cook et al (1995) estimated the 2D FD of the GM–WM boundary in patients with frontal lobe epilepsy (FLE) and temporal lobe epilepsy (TLE), observing that 9 out of 16 patients with FLE had abnormal FD values, while none of the patients with TLE had abnormal FD values.…”
Section: Resultsmentioning
confidence: 99%
“…Although the other 4 studies did not explicitly limit IQ scores in the exclusion/inclusion criteria, the mean IQ scores of the samples were significantly >70 ( 23 , 28 , 29 , 45 ). The other two included children with benign childhood epilepsy with centrotemporal spikes (BECTS) ( 25 , 44 ), who usually exhibited normal intelligence ( 58 60 ). The remaining 1 study limited samples to individuals with an IQ score >60, and of the 56 patients included, 6 were in the range of 60 to 69 and the others ≥70 ( 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 1 study limited samples to individuals with an IQ score >60, and of the 56 patients included, 6 were in the range of 60 to 69 and the others ≥70 ( 46 ). Considering that the IQ of the included sample may impact the results ( 60 ), subgroup analysis were conducted to examine social cognition deficits in samples with an IQ score >70.…”
Section: Methodsmentioning
confidence: 99%
“…However, the study results are not consistent. Considering the influence of duration, antiepileptic drugs and the range of patients' age, Li et al showed extensive cortical thinning in bilateral frontal, temporal regions, and limbic system, increased cortical gyrification in the left hemisphere and partial right hemisphere, and the decreased cortical gyrification in the left hemisphere, and increased sulcal depth in the left fusiform gyrus in drug-naive BECTS patients (12). On the other hand, negative correlation between age of onset and cortical thickness in the right precentral gyrus, cortical gyrification in the left inferior parietal gyrus, and negative correlation between VIQ and cortical gyrification in the left supramarginal gyrus have also been revealed.…”
Section: Introductionmentioning
confidence: 99%